Building Teacher Capacity for Inclusive Education: A Professional Development Model Using Technology and UDL - Ravindra Kumar Kushwaha; Chandan Singh (IJRAEL: International Journal of Religion Education and Law, 2023)
This study proposes a professional development model for building Teacher capacity in Inclusive Education, utilizing technology and Universal Design for Learning (UDL) principles. The model was developed based on a review of literature on inclusive education, teacher professional development, technology integration, and Universal Design for Learning (UDL). The proposed model includes three phases: (1) pre-training activities, (2) training activities, and (3) post-training activities. Pre-training activities involve a needs assessment, goal setting, and preparation for the training. The training activities include synchronous and asynchronous online sessions, collaborative activities, and self-paced learning modules. The post-training activities focus on ongoing support, coaching, and evaluation. The proposed model incorporates Universal Design for Learning (UDL) principles to ensure that the training is accessible and effective for all teachers, regardless of their learning preferences or disabilities. Universal Design for Learning UDL works on three principles. The model incorporates the use of technology to facilitate the training and support phases, including an online learning platform and virtual coaching sessions. The UDL framework is used as a guiding principle throughout the model, ensuring that teachers have the tools and knowledge to design instruction that is accessible to all students, regardless of their learning needs or abilities. The study concludes that the proposed professional development model can effectively build teacher capacity for inclusive education and promote positive outcomes for students with diverse needs.